Analisis Pengaruh Magnesium Terhadap Pertumbuhan Vegetatif Kopi Arabika Varietas Sigarar Utang - Adriani Saurnida Siahaan Asianna; Rolan Siregar; Halus Satriawan (Politeknik Negeri Lampung., 2025)
South Tapanuli , North Tapanuli, Humbang Hasundutan and Dairi districts are in the Sumatera Utara Province. These four districts are producers of the Arabica debt variety of Arabica coffee and are the source of the varieties used as plant material for research. The aim is to determine the dosage of magnesium fertilizer through the soil and leaves on the vegetative growth of Arabica coffee of the Sigarar Utang Variety which experiences symptoms of magnesium deficiency. This research was designed by factorial Completely Randomized Block Design consisting of 2 factors, namely the dose of magnesium fertilizer 4 levels, namely M0 (0 g / plant), M1 (10 g / plant), M2 (20 g / plant) and M3 (30 g / plant) applied through the soil and leaves and the source of the variety source 4 levels, namely B1 (South Tapanuli), B2 (North Tapanuli, B3 (Humbang Hasundutan), B4 (Dairi) with 3 replications. The variables observed were the increase in plant height (cm), Leaf Area (cm2) and Magnesium nutrient content in coffee leaf tissue (%). The results showed that the treatment of magnesium fertilizer doses through soil and leaves and the source of the Sigarar Utang Variety had a significant effect on the results. The level of magnesium fertilizer dose treatment of 30 g / plant applied through soil and leaves resulted in maximum increase in plant height (cm), leaf area (cm2) and magnesium nutrient content in coffee leaf tissue (%). The highest and best source of the Sigarar Utang Variety was produced by varieties from Dairi district and the response of the plant to the application of magnesium fertilizer was more maximal absorption of nutrients through soil and leaves, so that the magnesium nutrient content in the tissue leaves (%) and plant height increase (cm) are higher than the source level of other Sigarar Utang Varietties